Eksplorasi Perencanaan Keuangan Generasi Muda: Pendekatan SEM PLS - Abubakar, Akhmad H; Subaki, Ahmad; Zamzany, Faizal Ridwan; Fikri Hidayat (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This study aims to reveal the financial planning actions taken by the younger generation. The factors taken to measure the financial planning of the younger generation are Financial Literacy, Trust, FOMO, and Mental Accounting. Method: This research uses a quantitative method, where researchers use numbers based on a Likert scale to answer the hypothesis proposed. The data collection method in this research uses non-probability sampling or voluntary sampling techniques. After distributing the questionnaires, a sample size of 140 respondents was obtained. The sample obtained was then analyzed using statistical software, namely Smart PLS 4.0. Research Finding: The findings obtained in this research are that the independent variables, namely financial literacy, trust, and fomo, have a positive and significant impact on the financial planning of the younger generation. Meanwhile, one other variable, namely mental accounting, has no effect on individual financial planning in the younger generation. When viewed from the impact of the existing correlation of the independent variable on the dependent variable, it has a value of 55.2 percent. The rest may be influenced by other variables that were not tested in this study. Theoretical contribution: This research contributes to the tendencies that can cause an individual to be influenced in deciding financial actions. Practitionel implication : Financial literacy, self-confidence, and mental accounting have an impact on individuals when doing financial planning. So that individuals must be able to protect themselves by understanding the factors that drive their decision making. The findings in this research can be taken into consideration in decision making by the government regarding financial education to the public. Apart from that, the findings from this research can also be input for financial service providers to provide understanding to users before using their financial products. Research limitation : This research was only conducted on the younger generation, namely the generation born between 1997 - 2010 or commonly known as generation Z. Therefore, these results cannot be used to make judgements about millennials or other generations. So these results cannot properly be an assessment of millennial society or other generations.